Concept Analysis of Vasectomy Method Selection Decisions: A Literature Review - Wahyu Wahyu; Enjelina Angela Fransiska Fanumbi; Wa Ode Vita Sumarta; Yuli Windarti; Asep Muhamad Nurhalim; Satriya Pranata; Siti Aisah; Aric Vranada (Indonesian Journal of Global Health Research, 2024)
Indonesia faces a significant challenge with a high population growth rate that affects development quality and family welfare. One solution is to increase male participation in the family planning program through contraceptive methods such as vasectomy. However, the acceptance rate of vasectomy is still low due to various factors. This study analyzes the factors influencing vasectomy acceptance by identifying its attributes, antecedents, and consequences. This study used Walker and Avant's concept analysis approach. The literature analyzed came from various databases, such as PubMed and ProQuest, with publications from 2019 to 2024. A total of 129 articles were found, and 24 articles met the inclusion criteria for further review. The analysis identified four main attributes that influenced the decision to choose vasectomy: knowledge, wife support, economic factors, and planning for the number of children. Antecedents such as age, education, and occupation shaped the level of knowledge, which, together with wife support and economic factors, influenced the family's decision to choose vasectomy. Consequently, vasectomy is accepted as an effective, safe, and cost-effective family planning method. This analysis highlights the need for comprehensive information and support to enhance men's participation in family planning programs through vasectomy.